2011
DOI: 10.5860/rusq.50n3.204
|View full text |Cite
|
Sign up to set email alerts
|

Citation Management Software

Abstract: When I was an undergraduate student, I used a portable word processor to type all my research papers. (Does this date me too much?) In other words, formatting and typing a paper was a lot of work and had to be properly thought out ahead of time. I would write each reference on an index card, consult my dog-eared copy of the Publication Manual of the American Psychological Association, 3rd edition, and carefully write out each element of the citation, double-checking my work along the way. An errant finger coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…More than 25 different bibliographic management programs exist; some are free and web-based while others have high registration fees and/or may be difficult to download or install (Mead & Berryman, 2010). Other authors have provided thorough overviews of citation or bibliographic management tools for academic libraries (Childress, 2011;Kern & Hensley, 2011); for this study, we were only concerned with two products in the bibliographic management game, RefWorks and EasyBib.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More than 25 different bibliographic management programs exist; some are free and web-based while others have high registration fees and/or may be difficult to download or install (Mead & Berryman, 2010). Other authors have provided thorough overviews of citation or bibliographic management tools for academic libraries (Childress, 2011;Kern & Hensley, 2011); for this study, we were only concerned with two products in the bibliographic management game, RefWorks and EasyBib.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers com-Open Access Library Journal pared features between two software programs [3] [8] Other researchers compared more software. Hensley [9], for example, examined the features, benefits, and drawbacks of four popular RMSs-RefWorks, EndNote, Zotero, and Mendeley-from the perspectives of both librarians and patrons. Likewise, Gilmour and Cobus-Kuo [10] compared four RMSs-CiteULike, RefWorks, Mendeley, and Zotero-in terms of their features and accuracy of generated bibliographies.…”
Section: Reference Management Softwarementioning
confidence: 99%
“…According to [22], the RefWorks reference management software is the web-based and compatible with the entire platform. However, [22] also indicated that user easily can adopt interface to export the references into RefWorks.…”
Section: B Refwork (Product Information)mentioning
confidence: 99%
“…According to [22], the RefWorks reference management software is the web-based and compatible with the entire platform. However, [22] also indicated that user easily can adopt interface to export the references into RefWorks. Furthermore, [22] stated that RefWorks reference management software can attach feature, researchers can upload up to 100 MB of different types of files, and administrator can increase limit up to 5GB.…”
Section: B Refwork (Product Information)mentioning
confidence: 99%
See 1 more Smart Citation